Investigation of the Peripapillary Choriocapillaris in Normal Tension Glaucoma, Primary Open-angle Glaucoma, and Control Eyes. Issue 8 (August 2021) - Bhalla, Mahadev; Heisler, Morgan; Mammo, Zaid; Ju, Myeong Jin; Sarunic, Marinko V.; Navajas, Eduardo V.; Warner, Simon; Schendel, Steven; Gill, Kulbir S.
Abstract : Precis: The peripapillary choriocapillaris (CC) was observed to be significantly impaired in normal tension glaucoma (NTG) subjects compared with normal controls using optical coherence tomography angiography (OCTA). Purpose: The aim was to quantitatively evaluate the peripapillary CC in NTG, primary open-angle glaucoma (POAG), and control eyes using OCTA. Materials and Methods: Ninety eyes (30 controls, 30 NTG, and 30 POAG) from 73 patients were imaged using the Zeiss Plex Elite 9000. Five repeat 3×3 mm OCTA scans were acquired both nasally and temporally to the optic disc and subsequently averaged. Four CC flow deficit (FD) measures were calculated using the fuzzy C-means approach: FD density (FDD), mean FD size (MFDS), FD number (FDN), and FD area (FDA). Results: Temporal NTG CC parameters were associated with visual field index and mean deviation ( P <0.05). The control group showed a significantly lower nasal FDD (nasal: 3.79±1.26%, temporal: 4.48±1.73%, P =0.03), FDN (nasal: 156.43±38.44, temporal: 178.40±45.68, P =0.02), and FDA (nasal: 0.22±0.08, temporal: 0.26±0.10, P =0.03) when compared with temporal optic disc. The NTG group showed a significantly higher FDD (NTG: 5.04±2.38%, control: 3.79±1.26%, P =0.03), FDN (NTG: 185.90±56.66, control: 156.43±38.44, P =0.04), and FDA (NTG: 0.30±0.14 mm 2, control: 0.22±0.08 mm 2, P =0.03) nasal to the optic disc compared with controls. Conclusions: Association between CC parameters and glaucoma severity in NTG, but not POAG subjects, suggests vascular abnormalities may be a potential factor in the multifactorial process of glaucoma damage in NTG patients.